Experience with counterpulsation in cardiac surgical patients. Issue 2 (February 1977) - Smith, G H; Morgan, W E
Abstract : At Sheffield Regional Cardiothoracic Unit, the AVCO intra-aortic balloon pump has been used on 25 occasions in 21 months. Of the 25 patients, 12 survived and left hospital. The procedure is particularly beneficial in patients who have suffered some failure of myocardial protection during operation and to those who are suffering from acute ischaemia or the sequelae of myocardial infarction. The place of preoperative counterpulsation is discussed. Patients with long-standing cardiac disease who have emergency surgery benefit less from counterpulsation. Those patients with chronic ischaemic damage to the heart have nothing to gain from the use of counterpulsation.